Enzyme-Inducing Antiseizure Medications and Hypovitaminosis D in Children with Epilepsy: A Cross-Sectional Study in West Sumatera, Indonesia - Trisna Yunita; Rahmi Lestari; Nice Rachmawati Masnadi; Eva Chundrayetti; Amirah Zatil Izzah; Indra Ihsan; Rinang Mariko (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background. Long-term antiseizure-medication (ASM) therapy can accelerate vitamin D catabolism via hepatic cytochrome P450 induction, predisposing children with epilepsy to hypovitaminosis D and its skeletal consequences; Indonesian tertiary-centre data remain scarce. Methods. This cross-sectional study examined the association between ASM class, number and duration and serum 25-hydroxyvitamin D [25(OH)D] in children aged 1–18 years at Dr. M. Djamil General Hospital, Padang, West Sumatera, between April and October 2025. Of 82 records screened, 77 were eligible; 25(OH)D was measured by enzyme-linked fluorescent assay, with hypovitaminosis D defined as <30 ng/mL. Associations were tested with Fisher–Freeman–Halton exact and chi-square tests, odds ratios, ANOVA, multivariable logistic regression and ROC analysis. Results. Hypovitaminosis D affected 48 children (62.3%; 95% CI 51.2–72.3), with mean 25(OH)D of 18.3±6.7 versus 41.6±11.2 ng/mL in deficient versus replete children. ASM class was significantly associated with vitamin D status (exact p=0.037; Cramér's V=0.283): all nine enzyme-inducing users were deficient, versus 56.0% non-enzyme-inducing and 58.1% combination (ANOVA p=0.045, η²=0.080). Neither ASM number (p=0.642) nor duration (p=0.348) was associated. Enzyme-inducing exposure carried the largest adjusted odds (adjusted OR 5.66, 95% CI 0.62–52.06), and the model discriminated moderately (AUC 0.685). Conclusion. Hypovitaminosis D is prevalent in Indonesian children with epilepsy and is most strongly linked to enzyme-inducing ASMs, supporting early routine 25(OH)D monitoring and supplementation from treatment initiation.